Global analysis reveals multiple pathways for unique regulation of mRNA decay in induced pluripotent stem cells - Neff, Ashley T.; Lee, Ju Youn; Wilusz, Jeffrey; Tian, Bin; Wilusz, Carol J.

(untitled) (Genome Research, 2012)
Pluripotency is a unique state in which cells can self-renew indefinitely but also retain the ability to differentiate into other cell types upon receipt of extracellular cues. Although it is clear that stem cells have a distinct transcriptional program, little is known about how alterations in post-transcriptional mechanisms, such as mRNA turnover, contribute to the achievement and maintenance of pluripotency. Here we have assessed the rates of decay for the majority of mRNAs expressed in induced pluripotent stem (iPS) cells and the fully differentiated human foreskin fibroblasts (HFFs) they were derived from. Comparison of decay rates in the two cell types led to the discovery of three independent regulatory mechanisms that allow coordinated turnover of specific groups of mRNAs. One mechanism results in increased stability of many histone mRNAs in iPS cells. A second pathway stabilizes a large set of zinc finger protein mRNAs, potentially through reduced levels of miRNAs that target them. Finally, a group of transcripts bearing 3′ UTR C-rich sequence elements, many of which encode transcription factors, are significantly less stable in iPS cells. Intriguingly, two poly(C)-binding proteins that recognize this type of element are reciprocally expressed in iPS and HFF cells. Overall, our results highlight the importance of post-transcriptional control in pluripotent cells and identify miRNAs and RNA-binding proteins whose activity may coordinately control expression of a wide range of genes in iPS cells.